ETIKA KONSUMSI DAN KESEJAHTERAAN DALAM PERSPEKTIF EKONOMI ISLAM - Rahmat Ilyas (Universitas Islam Negeri Sumatera Utara, 2016)
Consumption is a form of human economic behavior in human life. Every living thing must have activities including human consumption. In Islamic Economics customer satisfaction depends on the values of the religion to which he applied in routine activities are reflected in the money dibelanjakannya. Religious teachings which are run either prevent consumers from israf nature, because israf an extravagant nature consciously done to meet the demands of mere lust. Material and spiritual welfare is a goal to be achieved in the development process. This suggests that the success of the development must be achieved not only in the material aspect, but also in the spiritual aspect.